Hormonal control of metabolism in trauma and sepsis. - Frayn, K (1986)
The metabolic changes occurring after injury and in sepsis are still, more than 60 years after their relatively complete description, a cause of significant morbidity and mortality. Although many of their deleterious aspects can be overcome by active nutritional support, this is primarily an empirical means of treatment. The hormonal environment which produces these changes has not been fully elucidated, at least in part because so much of the work in this area has been plagued by the study of small heterogeneous groups of patients at different stages in their response, by a failure to measure the hormones most likely to be relevant, and by an almost universal failure to attempt to relate the endocrine to the metabolic changes observed. This picture is now changing for the better as more interest is centred on the responses to trauma, and the authors are at last in a position to formulate testable hypotheses about the endocrine control of metabolism in trauma and sepsis.